Preparation of Contingency Trajectory Operation for the Korea Pathfinder Lunar Orbiter - Bang, Jun; Hong, SeungBum; Bae, Jonghee; Song, Young-Joo; Lee, Donghun (Journal of astronomy and space sciences, 2023)
The Korea Pathfinder Lunar Orbiter (KPLO), also known as Danuri, successfully entered its mission orbit on December 27, 2022 (UTC), and is currently performing its mission smoothly. To mitigate potential contingencies during the flight and to navigate the spacecraft into the desired lunar orbit, the KPLO flight dynamics (FD) team analyzed major trajectory-related contingencies that could lead to the violation of mission requirements and prepared operational procedures from the perspective of trajectory and FD. This paper presents the process of preparing contingency trajectory operations for the KPLO, including the identification of trajectory contingencies, prioritization results, and the development of recovery plans and operational procedures. The prepared plans were successfully applied to address minor contingencies encountered during actual operations. The results of this study will provide valuable insights to FD engineers preparing for space exploration mission operations.